Sustainable Tourism and The Roles of Tour Guides in Destinations: A Qualitative Case Study in Turkey - Evrim Bilgi; Volkan Kalın; Özlem Güzel; Eren Nacak (Journal of Economy Culture and Society)
The sustainable tourism approach is the way to ensure a destination’s development and protec-tion. Since there are important links between the visitor and the destination, tourist guides may contribute to the destination’s resources management and economic and socio-cultural impact. They could set a deep contact with tourists in destinations and have positive results on tourist sustainable behaviors. The aim of the study is to identify the dimensions of the roles attributed to tourist guides in the promotion of sustainable tourism and to determine the content of these roles within an exploratory perspective. In this research, the qualitative research method has been adopted in the phenomenology research design in order to reveal the meanings that tour guides have experienced. The data was obtained through deep-interviews with tourist guides and evalu-ated with descriptive analysis technique. According to the findings, the roles of the tourist guides are dimensioned as “adopting consulting role, taking over inspection, sustainability training, rais-ing tourists’ awareness, promotion of the local economy, and sustainable tour management” within the context of sustainable tourism development. The paper indicates the contributions to the tourism literature with the determination of roles tourist guides serve in the promotion of sus-tainable tourism in detail, as limited studies have been conducted in Turkey.